Role of APACHE-II Score in Predicting The Incidence of Ventilator-Associated Pneumonia in Intensive Care Unit Patients - Rehman, Sami Ur; Saeed, Unaiza; Ali, Asif; Malik, Muhammad; Ghani, Saran; Rehman, Eesha (Biological and Clinical Sciences Research Journal, 2025)
A prevalent nosocomial infection in the intensive care unit (ICU) is ventilator-associated pneumonia (VAP). VAP is defined as pneumonia in individuals with invasive mechanical ventilation during the preceding 48 hours; it affects 5–40% of patients with invasive mechanical ventilation. These scoring systems forecast the mortality, hence the disease’s prognosis, which is very important in limited health resources and an increased cost of health management. ICU staff and doctors are highly recommended to be familiar with using the APACHE-II scoring system. The three main components of the APACHE-II score are Acute Physiology scores (APS), age scores, and chronic health scores, generating a score from 0 to 71. These 12 measurements are measured within 24 hours of ICU admission. APACHE-II shows a better prediction of hospital outcomes than SAPS-II. So, the APACHE-II score can be used as an ICU standard. A study by Sutiono et al. in Indonesia stated that an APACHE-II score greater than 15 is linked with a higher risk of VAP. Objective: To see the APACHE-II score’s role in predicting ventilator-associated pneumonia incidence. Methods: This is a retrospective Cross-sectional Study done at the surgical ICU of Doctors Hospital and Medical Centre, Lahore, Pakistan, during the 18 months from 1st January 2022 to 30th June 2023. After the Approval to conduct this study was obtained from the hospital’s ethical committee (can be presented on request), data were collected manually and filled in tables in a Microsoft Office Word Document. Data was presented in the form of frequency (Percentages). Exclusion criteria for this study were patients aged less than 16 years, with a stay of less than 24 hours, and those who did not have all 19 physiological parameters. All patients over 16 years who stayed in the ICU for more than 24 hours were included in this study. Results: 293 patients were put on mechanical ventilation in the Surgical I.C.U. of Doctors Hospital and Medical Centre over the study period. Out of these 293 patients who were put on mechanical ventilation, 46 (15.69%) patients developed ventilator-associated pneumonia (VAP). Of 46 patients, 31 (67.4%) survived, and 15 (32.6%) expired. The prevalence of micro-organisms causing VAP is as follows: Pseudomonas 11(23.9%), Klebsiella 10 (21.7%), Acinetobacter 9 (19.5%), Candida albicans 6 (13%), Burkholderia 3 (6.5%), Staphylococcus 3 (6.5%), E. coli 2 (4.34%), Proteus mirabilis 1 (2.2%) and Enterobacter cloacae 1 (2.2%). Patients are then divided into two groups (those with APACHE-II score <20 and those with APACHE-II Score >20) to see the correlation between APACHE-II and VAP incidence. Patients with APACHE-II scores of more than 20 are 90 (30.7%), and 203 patients have less than 20. Of the group with APACHE Score <20, 18 (8.86%) developed VAP, and of the group with APACHE-II Score >20, 28 patients (31%) had developed VAP. Conclusion: The APACHE-II Scoring system is a good predictor of Ventilator-associated Pneumonia in intensive care unit settings. An APACHE-II score of more than 20 is a higher risk of developing ventilator-associated pneumonia than patients with an APACHE-II score of less than 20.